Clinical Instructors’ Teaching Performance: A Framework for Enhancement Activities - Cadosales, Maria Nancy Q. (JPAIR Multidisciplinary Research, 2009)
Clinical instructors affect the scholastic life of the nursing students. Their personal and professional skills affect the students’ actual laboratory performance in the hospitals or communities where they provide nursing care. It is the main purpose of this study to evaluate and describe the clinical instructors’ teaching performance for the second semester of the academic year 2007 - 2008. The students evaluated their clinical instructors’ professional decorum and interpersonal skills and the clinical teaching skills like planning and organizing, supervision, evaluation, and the use of English language. It was found in the study that the clinical instructors were rated very satisfactory in their professional decorum and interpersonal skills over their clinical teaching skills. There are areas rated low (4.15 and below) and these are the bases for proposed framework for enhancement activities.